The history of the death penalty in Colorado - Radelet, Michael L. (Timberline books, 2017)
"Radelet chronicles the details of each capital punishment trial and execution that took place in Colorado since 1859. Radelet accounts the debates and struggles over the use of the death penalty, placing the hundreds of cases into the context of a gradual worldwide trend away from this punishment"--Provided by publisher